Peran Orang Tua Dalam Menanamkan Nilai-Nilai Agama Islam pada Anak dI SDN Sukamahi 02 - Nurtupia Hasyifa (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2022)
The role of parents has an important position in the formation of children, such as character, attitude, knowledge, reasoning and so on. The family as a place of socialization and having a position of religious values ​​is the basis for children to behave in life in the future. The focus of this research is how the role of parents in instilling the values ​​of religious education in children, how the role of parents in instilling religious values ​​in children, and the role of parents in instilling moral values ​​in children at SDN Sukamahi 02. The method used used is a qualitative research with the type of research is a descriptive study. Data collection techniques used are observation, interviews, and documentation. Based on the results of the study, in instilling the values ​​of Islamic religious education in instilling educational values ​​in children, in this case parents at SDN Sukamahi 02 have played an important role in instilling religious values ​​in their children through approaches and interactions with children. In addition, parents have considered it important in instilling religious values ​​in children, because religion is the foundation in life, so that children become pious and pious. And the way parents instill religious values ​​in children is by introducing the existence of God to children, being a good example and making direct implementations with a good attitude to children. In instilling the values ​​of worship, parents at SDN Sukamahi 02 motivate, direct, teach and provide examples of the importance of worship in religious life, both in teaching how to pray, performing ablution, supervising children when praying so that they are accustomed since childhood to worship Allah. S.W.T. As for instilling moral values, parents at SDN Sukamahi 02 are to set a good example or example to their children and teach children to get used to living a good moral life. Keywords: The Role of Parents, Instilling Religious Values